2019
DOI: 10.1002/ijgo.12904
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta‐analysis of thermal coagulation compared with cryotherapy to treat precancerous cervical lesions in low‐ and middle‐income countries

Abstract: Background Thermal coagulation is gaining popularity for treating cervical intraepithelial neoplasia (CIN) in screening programs in low‐ and middle‐income countries (LMICs) due to unavailability of cryotherapy. Objectives Assess the effectiveness of thermal coagulation for treatment of CIN lesions compared with cryotherapy, with a focus on LMICs. Search strategy Papers were identified from previous reviews and electronic literature search in February 2018 with publication date after 2010. Selection criteria Pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 60 publications
0
24
0
1
Order By: Relevance
“…Meta-analyses demonstrated that the double-freeze method of cryotherapy and thermal ablation are effective treatments for CIN lesions [10][11][12][13]. Our experiments underline the small differences in tissue depth necrosis between both treatment modalities.…”
Section: Interpretation Of Resultsmentioning
confidence: 60%
See 2 more Smart Citations
“…Meta-analyses demonstrated that the double-freeze method of cryotherapy and thermal ablation are effective treatments for CIN lesions [10][11][12][13]. Our experiments underline the small differences in tissue depth necrosis between both treatment modalities.…”
Section: Interpretation Of Resultsmentioning
confidence: 60%
“…Previous studies showed that cure rates of CIN lesions in patients in LMICs do not differ significantly between cryotherapy and thermal ablation, demonstrating that both treatment modalities are effective [10][11][12][13]. However, there is no consensus on the treatment protocol for thermal ablation with temperatures ranging from 100 to 120°C, duration of treatment from 20 to 60 s and the number of treatment cycles from single to repeated application ranging from 2 to 5 cycles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It may be the case that providers were more hesitant to reveal their centers’ limitations at the site assessments–which were quality check-ins asking them to quantify barriers to care specifically at their sites–than in the surveys, whose stated purpose was to elicit providers’ impressions about barriers to care more generally. Known challenges in the costs and availability of cryotherapy have led to the development and endorsement by the WHO of thermal ablation, an alternative treatment for cervical dysplasia that will potentially address some of these challenges [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…(4) In terms of immune functions, basic and clinical studies have confirmed that cryotherapy can significantly improve the contents of OKT3+ and OKT4+ and the ratio of OKT3+/OKT4+ in immune cells, significantly increase the expression of IL-2R, and improve the immune function of patients [ 4 , 5 ]. Cryotherapy has been widely used in various diseases in clinic with good outcomes, including prostate cancer [ 6 ], irreversible pulpitis [ 7 ], esophageal cancer [ 8 ], cervical cancer [ 9 ]. But the efficacy of cryotherapy in combination with systemic chemotherapy in lung cancer patients is unclear.…”
Section: Introductionmentioning
confidence: 99%